Deep learning prediction of proton and photon dose distributions for paediatric abdominal tumours. (March 2021) - Guerreiro, F.; Seravalli, E.; Janssens, G.O.; Maduro, J.H.; Knopf, A.C.; Langendijk, J.A.; Raaymakers, B.W.; Kontaxis, C.
Highlights: Deep-learning networks for prediction of PBS and VMAT doses were established. Relative errors between planned and predicted doses were minimal in the target. Strong correlation ( r > 0.9) was found between planned and predicted DVH metrics. The networks classified the PBS dosimetric benefit over VMAT with 98% precision. Proposed networks can accurately predict the treatment modality selection outcome. Abstract: Objective: Dose prediction using deep learning networks prior to radiotherapy might lead tomore efficient modality selections. The study goal was to predict proton and photon dose distributions based on the patient-specific anatomy and to assess their clinical usage for paediatric abdominal tumours. Material and methods: Data from 80 patients with neuroblastoma or Wilms' tumour was included. Pencil beam scanning (PBS) (5 mm/ 3%) and volumetric-modulated arc therapy (VMAT) plans (5 mm) were robustly optimized on the internal target volume (ITV). Separate 3-dimensional patch-based U-net networks were trained to predict PBS and VMAT dose distributions. Doses, planning-computed tomography images and relevant optimization masks (ITV, vertebra and organs-at-risk) of 60 patients were used for training with a 5-fold cross validation. The networks' performance was evaluated by computing the relative error between planned and predicted dose-volume histogram (DVH) parameters for 20 inference patients. In addition, the organs-at-risk mean dose difference between modalities was calculated using planned and predicted dose distributions (ΔDmean = DVMAT -DPBS ). Two radiation oncologists performed a blind PBS/VMAT modality selection based on either planned or predicted ΔDmean . Results: Average DVH differences between planned and predicted dose distributions were ≤ |6%| for both modalities. The networks classified the organs-at-risk Dmean difference as a gain (ΔDmean > 0) with 98% precision. An identical modality selection based on planned compared to predicted ΔDmean was made for 18/20 patients. Conclusion: Deep learning networks for accurate prediction of proton and photon dose distributions for abdominal paediatric tumours were established. These networks allowing fast dose visualisation might aid in identifying the optimal radiotherapy technique when experience and/or resources are unavailable.